Relationship of comorbid factors diabetes mellitus with oxygen saturation (SaO2) among people with Covid-19 in the Quarantine House - M. Hanif Prasetya Adhi; Endiyono Endiyono (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2022)
Background: The Covid-19 has infected a hundred people countries, in Indonesia at 8.9%, this figure is the highest in Southeast Asia. The phenomenon, shows that nursing volunteers who work in quarantine place for Covid-19 patients not maintenance to screen of SaO2 value of Covid-19 patients, even though the impact of happy hypoxia on mortality will be high if the oxygen saturation value is below the normal value. Comorbid factors, Diabetes Mellitus can worsen the physical condition and clinical assessment thereby increasing mortality.Objectives: The purpose of research to determine the relationship between age, gender, and comorbid factors with the value of oxygen saturation (SaO2) in Covid-19 patients at the Baturaden Quarantine Place. Methods: This study is a quantitative study using an analytical observational method with a crossectional approach. The sample in this study used random sampling of 93 respondents with the Fisher Exact test.Results: The results of this study, fisher exact test obtained with a p-value = 0.007, there is a relationship between the respondent's comorbidity factor and SaO2 in patients with confirmed COVID-19. Respondents with 95-100% SaO2 who have comorbid factors as many as 20 respondents (21.5%) are fewer than respondents who do not have comorbid factors as many as 29 respondents (30.5%). Blood glucose levels can increase viral replication and suppress the antiviral immune response. This causes DM patients to be more likely to be malnourished and susceptible to cytokine storms that cause a rapid deterioration of clinical conditions compared to non-diabetic patients.Conclusions: The comorbid factors will increase mortality of COVID-19 patients due to risk factors, comorbid of diabetes mellitus factors, with COVID-19 associated with advanced age, obesity, chronic systemic inflammation, increased coagulation, which can significantly increase blood pressure, indirectly lead to more severe complications due to COVID-19.